2019
DOI: 10.3390/polym12010010
|View full text |Cite
|
Sign up to set email alerts
|

PLA/PA Bio-Blends: Induced Morphology by Extrusion

Abstract: The effect of processing conditions on the final morphology of Poly(Lactic Acid) (PLA) with bio-based Polyamide 10.10 (PA) 70/30 blends is analyzed in this paper. Two types of PLA were used: Commercial (neat PLA) and a rheologically modified PLA (PLA REx ), with higher melt elasticity produced by reactive extrusion. To evaluate the ability of in situ micro-fibrillation (µf) of PA phase during blend compounding by twin-screw extrusion, two processing parameters were varied: (i) Screw speed rotation (rpm); and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…Despite its great potential, PLA still has limitations, such as its brittleness, its reduced service temperature range, and its high instability during processing where good melt strength is required. There is a large amount of research dedicated to solving these drawbacks with the aim of expanding its application window to become a commodity or even an engineering thermoplastic [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its great potential, PLA still has limitations, such as its brittleness, its reduced service temperature range, and its high instability during processing where good melt strength is required. There is a large amount of research dedicated to solving these drawbacks with the aim of expanding its application window to become a commodity or even an engineering thermoplastic [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It can be easily processed with conventional process such as extrusion, spinning, injection and compression molding [12][13][14][15]. However, its high brittleness limits its use, thus different strategies are tested in order to improve its toughness [16][17][18][19]. Among them, blending of PLA with PBAT has shown promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Grace provided a systematic study about the variation of the critical capillary number as a function of the viscosity ratio in shear and elongational flow, demonstrating that the extensional flow is more effective than shear in deforming and breaking up the droplets [142]. In fact, as is observable in Figure 14, at a fixed viscosity ratio, a smaller value of critical capillary number is obtained in elongation than in shear; moreover, in contrast to shear flow, the elongational flow is able to induce the breakup of droplets at viscosity ratios higher than 4 [143]. The results obtained by Grace were confirmed for different polymer-based blends [144,145]; in particular, Utracki et al [135] reported that the efficiency of the elongational flow in inducing morphology evolution dramatically increases for viscosity ratio beyond 3, leading to the deformation of the dispersed droplets to long fibrils.…”
Section: Morphology Evolution Of Polymer-based Blends Under Elongational Flowmentioning
confidence: 75%